2014
DOI: 10.1063/1.4903278
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency noise peak near magnon emission energy in magnetic tunnel junctions

Abstract: We report on the low frequency (LF) noise measurements in magnetic tunnel junctions (MTJs) below 4 K and at low bias, where the transport is strongly affected by scattering with magnons emitted by hot tunnelling electrons, as thermal activation of magnons from the environment is suppressed. For both CoFeB/MgO/CoFeB and CoFeB/AlOx/CoFeB MTJs, enhanced LF noise is observed at bias voltage around magnon emission energy, forming a peak in the bias dependence of noise power spectra density, independent of magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Since it appears only close to the magnetic phase transition at ∼118 K and disappears in the PM phase, it is evident that the Lorentzian component is associated with the magnetic phase transition and subsequent subtle change in its resistive behavior, as shown in Figure d. The nature of noise spectra is generally affected by the change in material phases in terms of electrical, structural, and magnetic properties. ,, When the material undergoes a phase change, the noise behavior can appear in the Lorentzian form due to the creation of a two-level system. In our case, at 118 K, the material undergoes a transition from the PM to the AFM phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it appears only close to the magnetic phase transition at ∼118 K and disappears in the PM phase, it is evident that the Lorentzian component is associated with the magnetic phase transition and subsequent subtle change in its resistive behavior, as shown in Figure d. The nature of noise spectra is generally affected by the change in material phases in terms of electrical, structural, and magnetic properties. ,, When the material undergoes a phase change, the noise behavior can appear in the Lorentzian form due to the creation of a two-level system. In our case, at 118 K, the material undergoes a transition from the PM to the AFM phase.…”
Section: Resultsmentioning
confidence: 99%
“…The noise data on magnetic materials reveal the appearance of non-Gaussian RTS noise from thermally generated microscopic processes. , RTS noise involves the dominance of a single fluctuator of either electrical or magnetic origin that switches between two states. , The appearance of RTS noise has also been attributed to magnetic domain fluctuations and domain–domain interactions. , Among a few reported studies of LFN in AFM materials, it was found that thermally agitated magnetic noise in Co-based amorphous and polycrystalline alloys is of 1/ f type . Note that 1/ f and RTS noises are dominant noise sources in magnetic sensors and magnetic tunnel junctions, , and the noise data are generally used as a metric to measure the sensitivity and detectability of the device under varying magnetic fields …”
Section: Introductionmentioning
confidence: 99%